2017
DOI: 10.1007/s11606-016-3944-3
|View full text |Cite
|
Sign up to set email alerts
|

The Coming Primary Care Revolution

Abstract: The United States has the most expensive, technologically advanced, and sub-specialized healthcare system in the world, yet it has worse population health status than any other high-income country. Rising healthcare costs, high rates of waste, the continued trend towards chronic non-communicable disease, and the growth of new market entrants that compete with primary care services have set the stage for fundamental change in all of healthcare, driven by a revolution in primary care. We believe that the coming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
56
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 53 publications
0
56
0
3
Order By: Relevance
“…Numerous studies have shown that primary care contributes to improved population health, lower costs, and greater equity . Therefore, primary care plays an increasingly important role in the healthcare system as the population ages rapidly and becomes more diversified …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have shown that primary care contributes to improved population health, lower costs, and greater equity . Therefore, primary care plays an increasingly important role in the healthcare system as the population ages rapidly and becomes more diversified …”
Section: Introductionmentioning
confidence: 99%
“…Measuring and improving the quality of primary care are essential for ensuring high‐quality and efficient care; however, small medical facilities are often left out of quality improvement activities compared to large hospitals. The quality of primary care in small medical facilities has therefore drawn increasingly close attention …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, the primary care should be derived by key principals such as: (i) relationships to serve as the bedrock of value fostered by teams, improved clinical operations, and technology; (ii) patients and non-physicians engaged in most aspects of healthcare; and (iii) the whole-person care including health behaviors and social services [7]. In alignment with this vision, we propose the Smart Primary Care Environment (SPCE) as a health ecosystem of interacting objects, e.g.…”
Section: Journal Of Healthcare Communications Issn 2472-1654mentioning
confidence: 99%
“…2 With the development of new healthcare delivery and payment models and the increasing medical complexity of the primary care patient, PCPs are facing greater pressure to deliver coordinated, integrated, team-based care to achieve improved population health. 3 While physical therapists are sometimes mentioned in team-based models of primary care, little empirical data are available on the extent to which PCPs engage physical therapists in patient care. Current guidelines recommend physical therapy (PT) as an essential component of first-line treatment for many musculoskeletal conditions.…”
Section: Introductionmentioning
confidence: 99%